Isotropic, high-resolution, whole-chest inversion recovery contrast-enhanced magnetic resonance angiography in under 4.5 min using image-based navigator fluoro trigger - Craft, Jason; Parikh, Roosha; Cheng, Josh Y.; Diaz, Nancy; Kunze, Karl P.; Schmidt, Michaela; Neji, Radhouene; Leung, Amanda; Weber, Suzanne; Weber, Jonathan; Carter, Timothy; Biso, Sylvia; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSerial assessment of the thoracic aorta with magnetic resonance angiography (MRA) is desirable due to 3D volumetric dataset, high spatial resolution, and lack of ionizing radiation. Electrocardiogram (ECG) gated, contrast-enhanced (CE), inversion recovery gradient echo MRA is efficient and historically provides low artifact burden, but the window for imaging with weak albumin binding extracellular gadolinium based contrast agents is small. Our purpose was to acquire whole-chest gated CE-MRA with 1.2 mm3 resolution using image-based navigator (iNAV) for motion correction/contrast monitoring, and variable density sampling in 4–5 min. Image quality and vessel diameter reproducibility are assessed against time resolved MRA (TR-MRA).MethodsiNAV CE-MRA and TR-MRA were obtained prospectively in 40 patients and reviewed by 3 blinded cardiologists for vessel diameter and image quality rated on a four point scale: (1) non-diagnostic; (2) poor-significant blurring; (3) good-mild blurring; and (4) excellent. Reproducibility and image quality were evaluated using the concordance correlation statistic and Cohen's kappa with mean differences evaluated using paired t-tests and repeat-measures ANOVA.ResultsiNAV CE-MRA scan time was 4.2 ± 0.7 min. iNAV CE-MRA quality score was higher (p < .001); average difference was 1.4 ± .08 at the sinus of Valsalva (SOV), 1.3 ± .08 at the sinotubular junction (STJ), and .87 ± .10 at the ascending aorta (AAO). Major/minor diameter interobserver agreement was better for iNAV CE-MRA (SOV ICC = .87–.93; STJ ICC = .95–.96; AAO ICC = .96–.97) vs. TR-MRA (SOV ICC = .69–.82; STJ ICC = .78–.83; AAO ICC = .89), as was intraobserver agreement (SOV ICC = .93–.95; STJ ICC = .94–.96; AAO ICC = .96–.97) vs. TR-MRA (SOV ICC = .81–.88; STJ ICC = .72–.73; AAO ICC = .87–.93).ConclusioniNAV CE-MRA is feasible within a clinically reasonable scan time, provides superior image quality, and measurement reproducibility vs. TR-MRA.